SIMULATION OF OPERATIONAL CONDITIONS OF FASSIP-02 NATURAL CIRCULATION COOLING SYSTEM EXPERIMENTAL LOOP - Dr.Anhar Riza Antariksawan; Surip Widodo; Mulya Juarsa; Dedy Haryanto; Mukhsinun Hadi Kusuma; Nandy Putra (Jurnal Sains dan Teknologi Nuklir Indonesia (Indonesian Journal of Nuclear Science and Technology), 2018)
The natural circulation is considered in the design of emergency passive core cooling system in a nuclear power plant. In that context, in order to investigate the characteristics of the natural circulation, FASSIP-02 experimental loop is designed. This paper simulates the various operational conditions with different condition of the heater power, the pipe insulation and the expansion tank's valve using RELAP5 code. The objective is to obtain the best operational conditions of FASSIP-02 once it is built. The simulation results show that the until 50,000 s the steady state condition could not be achieved yet when the heater power greater than 10 kW. The pipe insulation reduced the heat loss to the environment and in turn it causes faster increase of the water temperature inside the pipe. While, if the expansion tank's valve is closed during the operation, the pressure inside the loop would increase, faster when the heater power is higher. It is concluded that in all cases to avoid the saturation condition, the heater power should be maintained lower than 10 kW, especially when the loop pipe is insulated.